The Art of Social Work Value Practice: A Case Study of Rural Governance in Yunnan, China - Liu, Fang; Sripokangkul, Siwach; Kamnuansilpa, Peerasit (Journal of Ecohumanism, 2024)
Social work has made significant contributions to poverty alleviation and rural development in China, with value practice at the core of achieving professional effectiveness. This study employs case interviews and a survey of secondary data to examine the value practice of social work in rural governance in Yunnan Province. Findings indicate that social work integrates with shaping of socialist values, governance that ‘wins the hearts’ through service, recognition of the ethical and moral values of ethnic minorities, the Confucian ethical care in rural society, and value consensus around a shared future for humanity. The complex connotation of social work value practice lies in the governance goal of integrating local, ethnic and personal identities into China’s national identity. Additionally, social work participates in international cooperation. The value practice carried out by social workers based on sociocultural contexts is a fluid and creative process in which social workers employ pragmatic rational logic to achieve governance objectives.